LANGUAGE AND SOCIAL CLASS OF ADOLESCENTS IN MUARA BASUNG VILLAGE, PINGGIR, BENGKALIS, RIAU - Ira Arini; Erni (SOSIOEDUKASI, 2026)
Language is the main means of social interaction that not only functions as a means of communication, but also as a reflection of the identity and social position of its speakers in society. This research is motivated by the phenomenon of diversity of economic and educational backgrounds in Muara Basung Village which is suspected to affect the variation in language use among adolescents, such as the use of slang, mixing codes, and shifting the level of formality. The purpose of this study is to describe the variation in language use by social class, identify differences in language style choices, and analyze the influence of the social environment on the way adolescents communicate. The method used in this study is a descriptive qualitative approach. The research subjects consisted of adolescents aged 13–18 years on Jalan Banjaran, Muara Basung Village. Data were collected through participatory observation techniques by observing direct verbal interactions as well as documentation in the form of recorded conversations and social media activities. The results of this study are expected to show that social class differences that include the economic and educational levels of parents significantly create different linguistic patterns in adolescents. In conclusion, the use of language in adolescents in Muara Basung Village functions as a status symbol that forms self-identity and shows closeness or distance between certain social groups. This research makes a theoretical contribution to the sociolinguistic development of the relationship between social structure and language variation.